1984
DOI: 10.1200/jco.1984.2.12.1327
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different forms of central nervous system prophylaxis on neuropsychologic function in childhood leukemia.

Abstract: A comparison of the late effects on intellectual and neuropsychologic function of three different CNS "prophylaxis" regimens was conducted in 104 patients treated for childhood acute lymphocytic leukemia. Of the children studied, 33 were randomized to treatment with intrathecal (IT) methotrexate alone, 36 to IT methotrexate plus 2,400 rad cranial irradiation, and 35 to IT methotrexate plus intravenous intermediate dose methotrexate. All patients were in their first (complete) continuous remission, were a minim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
1
2

Year Published

1994
1994
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(57 citation statements)
references
References 26 publications
0
54
1
2
Order By: Relevance
“…However, interpreting the results of clinical studies is complicated by the variation in systemic MTX exposure [14,16,[28][29][30]. Acute events associated with IV-MTX, with or without irradiation, include seizures and transient neurologic abnormalities such as focal sensorimotor deficits, and acute mental status changes occur in 5% to 10% of patients [31][32][33][34][35]. In the large Pediatric Oncology Group (POG) 9005 study approximately 8% of patients experienced acute clinical neurotoxicity after IV-MTX treatment alone; 75% of those patients with symptoms of neurotoxicity had qualitative MR imaging evidence consistent with a diagnosis of LE [27].…”
Section: Early Attempts To Quantify Imaging Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, interpreting the results of clinical studies is complicated by the variation in systemic MTX exposure [14,16,[28][29][30]. Acute events associated with IV-MTX, with or without irradiation, include seizures and transient neurologic abnormalities such as focal sensorimotor deficits, and acute mental status changes occur in 5% to 10% of patients [31][32][33][34][35]. In the large Pediatric Oncology Group (POG) 9005 study approximately 8% of patients experienced acute clinical neurotoxicity after IV-MTX treatment alone; 75% of those patients with symptoms of neurotoxicity had qualitative MR imaging evidence consistent with a diagnosis of LE [27].…”
Section: Early Attempts To Quantify Imaging Changesmentioning
confidence: 99%
“…Subtle cognitive deficits have been observed in as many as 60% of patients with ALL and are one of the most serious long-term adverse effects associated with MTX therapy [13,25,26,31,85,86]. Children treated for ALL with moderate-dose IV-or IT-MTX have shown declines in IQ scores comparable to those seen in children treated with low-dose cranial irradiation [17].…”
Section: Neurocognitive Impact Of Antileukemia Therapymentioning
confidence: 99%
“…Functions intrinsic to the nondominant hemisphere appear to be most affected. [4][5][6] It has been suggested that diffuse white matter pathology, caused by the neurotoxic treatment agents, may be the primary mechanism underlying the observed functional deficits. [7][8][9] CNS preventive therapy remains an important measure in the treatment of childhood ALL, but cranial irradiation is avoided today and is used only with patients with poor prognosis and under conditions of a CNS relapse.…”
Section: Introductionmentioning
confidence: 99%
“…In this type of condition the deterioration of cognitive functions can only be attributed to the iatrogenic effect of the treatment [10][11][12][13][14][15]. These studies, however, have one principal drawback: all the patients receive the same total dose (1,800 or 2,400 cGy), which is relatively low compared to that usually used in the treatment of ICT.…”
Section: Introductionmentioning
confidence: 99%